2020
DOI: 10.1007/s12274-020-2631-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-time in situ magnetic measurement of the intracellular biodegradation of iron oxide nanoparticles in a stem cell-spheroid tissue model

Abstract: The use of magnetic nanoparticles in nanomedicine keeps expending and, for most applications, the nanoparticles are internalized in cells then left within, bringing the need for accurate, fast, and easy to handle methodologies to assess their behavior in the cellular environment. Herein, a benchtop-size magnetic sensor is introduced to provide real-time precise measurement of nanoparticle magnetism within living cells. The values obtained with the sensor, of cells loaded with different doses of magnetic nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…These in cellulo methodologies have the advantage of including the proteins found in the biological environment, and among them, the proteins related to iron metabolism. Measurements of magnetism can be performed on this pool of cells and allow the quantitative monitoring of the nanoparticles' integrity in the long-term (over months) using techniques such as superconducting quantum interference device (SQUID), vibrating sample magnetometry (VSM), AC susceptibility, and magnetophoresis [41,176,177,228,229]. All rely on the measurement of the cells' magnetic moment, direct structural fingerprint of the nanoparticles in situ.…”
Section: Precise In Vitro Quantification Via Magnetometrymentioning
confidence: 99%
See 2 more Smart Citations
“…These in cellulo methodologies have the advantage of including the proteins found in the biological environment, and among them, the proteins related to iron metabolism. Measurements of magnetism can be performed on this pool of cells and allow the quantitative monitoring of the nanoparticles' integrity in the long-term (over months) using techniques such as superconducting quantum interference device (SQUID), vibrating sample magnetometry (VSM), AC susceptibility, and magnetophoresis [41,176,177,228,229]. All rely on the measurement of the cells' magnetic moment, direct structural fingerprint of the nanoparticles in situ.…”
Section: Precise In Vitro Quantification Via Magnetometrymentioning
confidence: 99%
“…Studies assessing the transformations of magnetic nanoparticles into stem cells have shown that the nanoparticles are most commonly endocytosed in endosomes that then fuse with lysosomes, where an acid-induced degradation takes place [36,41,176,229]. This progressive degradation has been quantitatively measured in cellulo, in a stem cell-spheroid model [41,176,229]. Under this specific culture model the stem cells stop dividing, start producing an extracellular matrix-rich environment, can be cultured for extend time frames (superior to a month), and can easily be handled due to their cohesive structure in the form of aggregates.…”
Section: Evidence Of a Progressive Degradation For Varying Nanoparticles Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously described the feasibility of magnetic guiding and showed that nanoparticle-loaded cells preferentially migrate to the limb on which an external magnet was placed. 54 [1][2][3]55 . (f-g) Effect of intracellular confinement on magnetic hyperthermia potential assessed by calorimetry.…”
Section: Endosomal Confinement Impacts Therapeutic and Imaging Functionsmentioning
confidence: 99%
“…Interestingly, some groups used stem‐cell spheroids as a tissue model to study the biodegradation of magnetic particles inside cells, in which case the cell stops dividing while the cell activities will not be affected; their results showed that the magnetic nanoparticles still existed after one month. [ 33–35 ] According to the comparison of intracellular iron contents retention time between two experimental cell incubation models (cell monolayer growth and cell spheroids), we speculate that the intracellular SPIONs retention time relies on the level of cell proliferation rather than biodegradation, which can be supported by the latest research. [ 36 ] When the stem cells were applied in vivo, they usually maintained a high level of proliferation; the measurement of intracellular iron content on single cell level is of great significance for evaluating the duration of detectable magnetic response signal generated by intracellular SPIONs.…”
Section: Resultsmentioning
confidence: 67%